The influence of leadership, organizational culture and loyalty on organizational performance at PCNU sidoarjo - Nasir, Maulana; M. Mustaqim, M. Mustaqim (Institute of Computer Science (IOCS), 2024)
Organizations run depending on the performance of their members. This research aims to find out directly the influence of leadership, organizational culture, and loyalty on the performance of organizational members at PCNU Sidoarjo. The method used is a quantitative method by processing data in the form of numbers using SmartPLS 4.0 to measure the results of the influence of leadership, organizational culture and loyalty on the performance of organizational members at PCNU Sidoarjo. The research was conducted using a random sampling method with a predetermined number of 130 respondents. The research results show that there is a significant influence between leadership, organizational culture and loyalty on the performance of organizational members at PCNU Sidoarjo